DECLARATION OF BASIC PRINCIPLES OF JUSTICE FOR VICTIMS OF CRIME AND ABUSE OF POWER TERHADAP PERLINDUNGAN KORBAN - Widiyantoro, S.H., M.M., M.H, Dr. Bambang (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2019)
ABSTRAK Digunakannya Kitab Undang-Undang Hukum Acara Pidana, membuat pelaku pidana sebagai subyek pemeriksaan tindak pidana. Dampak dari hal tersebut adalah sangat diperhatikan hak-hak pelaku pidana. Ini berbeda dengan korban tindak pidana yang masih kurang diperhatikan hak-haknya, khususnya dalam memperoleh ganti rugi materi. Jika dihubungkan dengan Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power, hal ini tentunya sangat tidak sesuai. Penelitian ini menggunakan pendekatan yuridis normatif, yaitu pendekatan penelitian dengan cara meneliti dan mengkaji objek penelitian melalui asas-asas hukum. Hasil penelitian ini menegaskan perlindungan korban tindak pidana dalam hal-hal yang mendasar, seperti pemberian ganti rugi kepada korban, baik dalam bentuk restitusi maupun kompensasi, telah diatur dalam Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power. Kata kunci: Perlindungan, Korban, Tindak Pidana. ABSTRACT The use of the Criminal Procedure Code makes criminal offenders the subject of a criminal act. The impact of this matter is that the criminal rights of the perpetrators are very concerned. This is different from victims of criminal acts whose rights are still lacking, especially in obtaining material compensation. If connected with the Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power, this is certainly not very appropriate. This study uses a normative juridical approach, which is a research approach by researching and studying the object of research through the principles of law. The conclusions are the protection of victims of criminal acts in fundamental matters, such as giving compensation to victims, both in the form of restitution and compensation, which has been regulated in the Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power. Keyword: Protection, Victim, Criminal Act.